Synthesis of 2'-modified nucleotides and their incorporation into hammerhead ribozymes. - Beigelman, L (1995)
Several 2'-modified ribonucleoside phosphoramidites have been prepared for structure-activity studies of the hammerhead ribozyme. The aim of these studies was to design and synthesize catalytically active and nuclease-resistant ribozymes. Synthetic schemes for stereoselective synthesis of the R isomer of 2'-deoxy-2'-C-allyl uridine and cytidine phosphoramidites, based on the Keck allylation procedure, were developed. Protection of the 2'-amino group in 2'-deoxy-2'-aminouridine was optimized and a method for the convenient preparation of 5'-O-dimethoxytrityl-2'-deoxy-2'-phthalimidouridine 3'-O-(2-cyanoethyl-N,N-diisopropylphosphoramidite) was developed. During the attempted preparation of the 2'-O-t-butyldimethylsilyl-3'-O-phosphoramidite of arabinouridine a reversed regioselectivity in the silylation reaction, compared with the published procedure, was observed, as well as the unexpected formation of the 2,2'-anhydronucleoside. A possible mechanism for this cyclization is proposed. The synthesis of 2'-deoxy-2'-methylene and 2'-deoxy-2'-difluoromethylene uridine phosphoramidites is described. Based on a '5-ribose' model for essential 2'-hydroxyls in the hammerhead ribozyme these 2'-modified monomers were incorporated at positions U4 and/or U7 of the catalytic core. A number of these ribozymes had almost wild-type catalytic activity and improved stability in human serum, compared with an all-RNA molecule.